The effect of HPMC - a cholesterol-lowering agent - on oral drug absorption in dogs - Reppas, C; G. Eleftheriou; Macheras, P.; Symillides, M; Greenwood, D; Dressman, JB (BIOPHARMACEUTICS & DRUG DISPOSITION, 1998)
The objective of this study was to evaluate the effects which hydroxypropylmethylcellulose (HPMC) may exert on oral drug absorption, in cases where this soluble fiber is administered to regulate blood lipid levels. Studies were conducted in vitro and in healthy female mongrel dogs using two different grades of HPMC, i.e. K8515 HPMC and ultra high molecular weight (UHMW) HPMC. The maximum plasma concentration, C-max, of paracetamol and both the C-max and the area under the concentration-time curve, AUC, of cimetidine were significantly decreased by the coadministration of 10 g of K8515 HPMC or 7.5 g of UHMW HPMC dissolved in 500 mL normal saline under fasting conditions. No statistically significant effects were observed on hydrochlorothiazide or mefenamic acid absorption. Based on in vitro data and previous studies it appears that reductions in gastric emptying and dissolution rate of paracetamol account for the effect observed in vivo. For cimetidine, a drug which can be absorbed from both the small and the large intestine, the indigestibility of HPMC in the colon in addition to the great reduction of dissolution rate led to reductions of both the C-max and AUC values. The long T-max values, even in the absence of HPMCs and the more modest reduction of the dissolution rate of hydrochlorothiazide by the HPMCs are thought to have precluded the observation of any significant alterations in the in vivo absorption profile. Owing to its erratic absorption, no statistically based conclusion could be drawn about the effects of coadministered HPMC on the oral absorption of the poorly soluble mefenamic acid. It is concluded that the effects of HPMCs on drug absorption in dogs are most pronounced for compounds with absorption profiles that are dependent on gastric emptying, i.e. compounds that are highly water soluble and that exhibit short T-max values. Compounds with long absorption profiles appear to be less susceptible to changes in absorption behavior due to coadministration of HPMCs. (C) 1998 John Wiley & Sons, Ltd.
Keywords: Absorption; cimetidine; Dogs; hydrochlorothiazide; hydroxypropylmethylcellulose; mefenamic acid; paracetamol; Viscosity